Comorbidities and Pregnancy Do Not Affect Local Recurrence in Patients With Giant Cell Tumour of Bone - Howard, Emma L (Cureus, 2020)
This study evaluates the relationship between pregnancy, comorbid conditions and giant cell tumour of bone. Furthermore, it examines if pregnancy and comorbid conditions affect the outcome following treatment for this tumour. A multi-centre retrospective review was conducted of consecutive patients with a confirmed histological diagnosis of giant cell tumour of bone between June 2012 and May 2017. A total of 195 patients were identified from two centres. Of these, 168 patients were treated with curative intent and had more than six months follow-up. Data were collected on pregnancy status, comorbid conditions, site of disease, surgical management and local recurrence rates. Statistical analysis included the Fisher exact test and Kaplan-Meier survival analysis. There were 72 females of childbearing age, of which 15 (21%) were currently pregnant or had been pregnant within the last six months. The pregnancy rate is higher than the highest reported pregnancy rate over the last 10 years (8.4%; Fisher test, p = 0.033). Women were more likely to have a comorbid condition than men (Fisher test, p < 0.002) and had a higher rate of autoimmune disease than the normal population (p = 0.015). Men were older than women (Wilcoxon test, p = 0.046) and had less risk of local recurrence (logrank test, p = 0.014). Pregnancy or comorbid conditions did not increase the local recurrence rate. Predictors for local recurrence included location in the distal radius (logrank test, p < 0.001), intralesional treatment (logrank test, p = 0.008) and age less than 40 (logrank test, p = 0.043). In conclusion, giant cell tumour of bone is more common in pregnant females and patients with immune disease. Comorbidities and pregnancy do not affect the local recurrence rate. Male patients over 40 years of age have a lower risk of local recurrence, and patients with disease in the distal radius have a high risk of recurrence.